Double-layer composite multifunctional CEI membrane structure and preparation method thereof

By constructing a double-layer composite multifunctional CEI film structure on the surface of the high-voltage positive electrode, using the inner film composed of LiF, Li2ZrO3 and LiNbO3 and the outer film composed of Li3PO4, multiple problems of the high-voltage positive electrode under long-term working conditions are solved, and the interface stability, electrochemical performance and mechanical performance are comprehensively improved.

CN119695165AActive Publication Date: 2025-03-25TIANFU JIANGXI LAB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411826725.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Under long-term working conditions, high-voltage positive electrodes are subject to problems such as intensified interfacial side reactions, dissolution and migration of transition metal ions, and mechanical damage caused by particle volume changes, resulting in rapid decline in battery performance and limiting its application potential.

Method used

It adopts a double-layer composite multifunctional CEI film structure, and the inner layer is composed of LiF, Li2ZrO3 and LiNbO3, providing chemical stability, lithium ion conductivity and stress relief functions; the outer layer is Li3PO4, which has high chemical stability and mechanical strength, and blocks the erosion of the positive electrode by the electrolyte.

Benefits of technology

Through the synergistic effect of inner and outer layers of materials, multiple challenges of high-voltage positive electrodes in complex working environments can be effectively solved, interface stability is comprehensively optimized, electrochemical and mechanical properties are improved, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695165A_ABST
    Figure CN119695165A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses a double-layer composite multifunctional CEI membrane structure and a preparation method thereof.The double-layer composite multifunctional CEI membrane structure comprises a composite inner-layer membrane and an outer-layer protective membrane which are sequentially constructed on the surface of a positive electrode from bottom to top; the composite inner layer film is prepared from LiF, Li2ZrO3 and LiNbO3; and the outer layer protective film is Li3PO4. According to the double-layer composite multifunctional CEI film, the inner layer is tightly attached to the surface of a positive electrode, and excellent lithium ion conductivity, chemical stability and transition metal shielding capacity are provided; the outer layer has good corrosion resistance, solvent resistance and mechanical strength, can effectively block the corrosion of electrolyte to the positive electrode, and slowly releases the influence of particle volume change on the film layer; the multifunctional synergistic effect is achieved through combination of functions of the inner layer and the outer layer, the interface stability of the high-voltage positive electrode material is optimized, the electrochemical performance and the mechanical performance are improved, and the interface stability and the cycle life of the high-voltage positive electrode are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a double-layer composite multifunctional CEI membrane structure and a preparation method thereof. Background Art

[0002] With the continuous development of electrochemical energy storage technology, high energy density batteries have become the core direction of the next generation of energy storage systems. Among them, high-voltage cathode materials have attracted widespread attention due to their high specific capacity and operating voltage performance. However, high-voltage cathodes face a series of complex problems under long-term working conditions, including intensified interfacial side reactions, dissolution and migration of transition metal ions, and mechanical damage caused by particle volume changes. These problems will cause rapid degradation of battery performance, significantly limiting its application potential.

[0003] Under high voltage conditions, the chemical reaction at the interface between the cathode material and the electrolyte becomes more intense, and the unstable byproduct deposition not only increases the interface impedance, but also reduces the reversibility of the electrochemical reaction. At the same time, transition metal ions are easily dissolved under high voltage conditions and migrate to the electrolyte or the surface of the negative electrode, triggering complex side reactions. In addition, the high-voltage cathode is accompanied by significant volume expansion and contraction during the charge and discharge process, and its internal particle structure is easily damaged by mechanical stress, resulting in particle cracking and damage to the interface film (CEI). This particle damage exposes a fresh interface, which further exacerbates the decomposition of the electrolyte and the continued occurrence of side reactions, forming a vicious cycle.

[0004] In response to these problems, researchers have proposed some interface modification strategies, including surface coating, in-situ film formation, and liquid phase coating. These methods alleviate the occurrence of side reactions and extend the cycle life of the battery to a certain extent by constructing a chemically stable interface film on the surface of the positive electrode. However, these strategies also have obvious defects. The surface coating method is prone to film damage during the volume change of the particles due to insufficient uniformity and density of the film layer; although in-situ film formation can improve interface compatibility, the film formation process is difficult to accurately control, resulting in the film layer functionality being difficult to meet the requirements; although liquid phase coating technology has improved the uniformity of the film layer, it usually exhibits low mechanical strength and is difficult to provide comprehensive functional protection. These technologies are mostly focused on improving the electrochemical stability of the interface, but pay insufficient attention to the mechanical damage caused by particle volume changes and the multifunctionality requirements of the interface film, making it difficult to meet the stability requirements of high-voltage positive electrodes in long-term cycles.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] The problem with the existing technology is that the current interface modification strategies are mostly focused on improving the electrochemical stability of the interface, which is difficult to meet the stability requirements of the high-voltage positive electrode in long-term cycles. A double-layer composite multifunctional CEI membrane structure and a preparation method thereof are provided, wherein the inner layer is tightly attached to the positive electrode surface, providing excellent lithium ion conductivity, chemical stability and transition metal shielding capability; the outer layer has good corrosion resistance, solvent resistance and mechanical strength, which can effectively block the erosion of the electrolyte to the positive electrode and slowly release the effect of particle volume changes on the membrane layer; the multifunctional synergistic effect is achieved by combining the functions of the inner and outer layers, optimizing the interface stability of the high-voltage positive electrode material, while improving the electrochemical and mechanical properties, and effectively improving the interface stability and cycle life of the high-voltage positive electrode.

[0007] The present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a double-layer composite multifunctional CEI membrane structure, including a composite inner layer membrane and an outer layer protective membrane sequentially constructed from bottom to top on the positive electrode surface;

[0009] The composite inner layer film includes LiF, Li 2 ZrO 3 and LiNbO 3 ;

[0010] The outer protective film is Li 3 PO 4 .

[0011] The multiple challenges faced by high-voltage cathode materials in complex working environments, including interfacial side reactions, mechanical failure caused by volume changes, decreased electrochemical stability, and increased interfacial impedance, are precisely the problems that the double-layer CEI membrane material of the present invention aims to solve. The present invention fully combines the performance characteristics of the inner and outer layer materials through the design of the double-layer membrane, and can achieve chemical, mechanical, and electrochemical multiple protection of the interface.

[0012] The inner layer film of the present invention is arranged on the positive electrode surface to directly respond to the interface reaction on the positive electrode surface, and adopts LiF, Li 2 ZrO 3 and LiNbO 3 The three components are composited as the inner layer material.

[0013] Among them, LiF has an extremely high band gap (8.72eV) and a low formation energy (-3.19eV / atom). The high band gap makes LiF have excellent electronic insulation under battery operating conditions, effectively preventing electron leakage and inhibiting electrolyte decomposition; its low formation energy ensures the chemical stability of the material, helps to prevent the dissolution of transition metal ions, and thus stabilizes the interface between the positive electrode and the electrolyte. LiF's low Poisson's ratio (0.2) indicates that the material has a small lateral deformation when subjected to force, which enables it to withstand large stresses and effectively alleviate the mechanical stress generated by the volume change of the positive electrode material during the charging and discharging process, maintaining the stability of the interface layer. In addition, LiF also has a high shear modulus (50GPa), which further enhances its ability to resist deformation and ensures the mechanical support of the film layer.

[0014] Li 2 ZrO 3 It has a medium band gap (3.73 eV) and a low formation energy (-3.038 eV / atom), which makes it chemically stable in the inner layer. 2 ZrO 3 The crystal structure provides a good lithium ion migration channel, which helps to improve ion conductivity and enhance the electrochemical stability of the membrane layer, ensuring stable operation of the battery at high voltage. 2 ZrO 3 The combination of Poisson's ratio (0.27) and shear modulus (55GPa) gives it a stronger stress relief ability, which can effectively cope with the mechanical stress caused by the volume change of the positive electrode material during the charging and discharging process, thereby reducing the interfacial stress and improving the overall stability of the film layer.

[0015] LiNbO 3 The band gap is 3.34eV, and it has a high Poisson's ratio (0.29) and good elasticity, which provides strong interface bonding ability in the inner layer film. 3 When subjected to stress, it can effectively adapt to lateral expansion while longitudinally stretching, thereby improving its adaptability to the interface structure and crack resistance. 3 It has excellent electrochemical stability, which helps to maintain the integrity of the interface film layer during long-term cycling and ensures the stability of the interface between the positive electrode and the electrolyte in a high-voltage working environment.

[0016] The inner layer film of the present invention utilizes LiF, Li 2 ZrO 3 and LiNbO 3 Under high operating voltage conditions, the interfacial film can effectively inhibit the decomposition of the electrolyte and the dissolution of transition metal ions, enhance the lithium ion conductivity, and improve the electrochemical stability of the positive electrode material.

[0017] The outer layer of the present invention is arranged outside the inner layer and directly contacts with the electrolyte. 3 PO 4 As outer layer material. 3 PO 4 Has a higher band gap (5.82eV), significantly higher than Li 2 ZrO 3 and LiNbO 3 , which means that it has excellent electronic insulation and can effectively prevent the flow of electrons, thereby reducing the decomposition reaction of the electrolyte and the occurrence of side reactions. 3 PO 4 It also has high chemical stability, which can effectively isolate the electrolyte from corroding the inner film and positive electrode particles, and ensure the long-term stability of the interface.

[0018] The double-layer composite multifunctional CEI membrane of the present invention has an inner layer directly in contact with the positive electrode particles, and utilizes LiF, Li 2 ZrO 3 and LiNbO 3 The excellent mechanical properties and low formation energy provide chemical barrier, electrochemical stability and stress relief functions. 3 PO 4 As a protective barrier, combined with its high band gap and excellent chemical stability, it further improves the corrosion resistance, mechanical strength and long-term stability of the overall film layer. Through the synergistic effect of the inner and outer layer materials, the double-layer composite multifunctional CEI membrane can effectively solve the multiple challenges of high-voltage positive electrodes in complex working environments, comprehensively optimize the interfacial stability of high-voltage positive electrode materials, and improve the electrochemical and mechanical properties at the same time, effectively improving the interfacial stability of high-voltage positive electrodes, thereby improving the overall performance and working stability of high-energy density batteries and extending the cycle life of high-energy density batteries.

[0019] In a specific embodiment, the composite inner layer film contains LiF, Li 2 ZrO 3 and LiNbO 3 The compound ratio is 1:0.5-1:0.5-1.

[0020] The ratio of each component in the present invention is creatively optimized to balance the advantages of each component. LiF provides good electrochemical stability and high electronic insulation, which can effectively prevent the decomposition of the electrolyte and the dissolution of transition metal ions. 2 ZrO 3 and LiNbO 3 The main purpose is to enhance the corrosion resistance, mechanical strength and thermal stability of the membrane. The proportional design ensures that the membrane has excellent stability and a long service life in a high voltage environment.

[0021] If Li 2 ZrO 3 If the ratio of LiNbO is too high, the membrane will be too dense, which may inhibit the migration of lithium ions, thereby affecting the ionic conductivity of the electrolyte and reducing the charge and discharge efficiency of the battery. 3 Too high a ratio may make the membrane too rigid, causing cracks in the membrane during battery charge and discharge, affecting the integrity of the membrane and the long-term stability of the battery. 2 ZrO 3 and LiNbO 3 If the ratio is too low, the corrosion resistance and thermal stability of the membrane are insufficient, and the membrane is prone to degradation or rupture under high voltage or high temperature environment, thus affecting battery performance and safety.

[0022] Therefore, the optimized ratio of 1:0.5-1:0.5-1 can improve battery performance while ensuring the comprehensive stability and reliability of the membrane, and effectively improve the overall safety and service life of the battery.

[0023] In a specific embodiment, the thickness of the composite inner layer film is 30 to 50 nm, and the thickness of the outer protective film is 50 to 80 nm.

[0024] The composite inner layer membrane is mainly responsible for the electrochemical reaction, provides ionic conductivity, and stabilizes the battery interface. Therefore, a thinner inner layer membrane helps to reduce the internal resistance of the battery, improve ionic conductivity, and maintain a higher electrochemical stability.

[0025] The main function of the outer protective film is to provide mechanical strength, prevent electrolyte decomposition, and prevent the dissolution of materials such as Co. Therefore, the thickness of the film needs to be moderate to ensure sufficient corrosion resistance and mechanical strength without affecting the overall performance of the battery.

[0026] In a second aspect, the present invention provides a method for preparing a double-layer composite multifunctional CEI membrane structure, comprising the following steps:

[0027] (1) coating the composite inner layer film on the positive electrode surface by a fluidized bed method;

[0028] (2) The outer protective film is prepared on the prepared composite inner layer film by magnetron sputtering.

[0029] In a specific embodiment, the specific method of step (1) is as follows:

[0030] LiF、Li 2 ZrO 3 and LiNbO 3 Mix according to the proportion and add to the dispersing solvent to make a uniform suspension;

[0031] The suspension is introduced into a fluidizing tank and sprayed onto the surface of the cathode material substrate to form a film layer;

[0032] The film layer is subjected to low temperature annealing treatment to obtain a composite inner layer film.

[0033] In a specific embodiment, the dispersion solvent is ethanol or water, and a surfactant is added to the suspension.

[0034] In a specific embodiment, the surfactant is one of sodium dodecyl sulfate, polyvinyl alcohol, and Tween series.

[0035] In a specific embodiment, the low temperature annealing treatment conditions are annealing temperature of 200-300° C. and annealing time of 1-2 h.

[0036] In a specific embodiment, the specific method of step (2) is as follows:

[0037] The cathode material substrate with the prepared composite inner layer film is placed in the magnetron sputtering equipment, and the target material is set as Li 3 PO 4 , sputtering process parameters: argon is used as the sputtering gas in the chamber, the pressure is 0.8-1.2Pa, the sputtering power is 50-120W, the substrate temperature is 100-150℃, and the sputtering time is 20-40min; Li is deposited on the coated composite inner layer film 3 PO 4 Membrane layer;

[0038] Opposite 3 PO 4 The film layer is subjected to low temperature annealing treatment to obtain an outer protective film.

[0039] In a specific embodiment, Li 3 PO 4 The low-temperature annealing treatment conditions of the film layer are annealing temperature 200-300°C and annealing time 1-2h.

[0040] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0041] 1. A double-layer composite multifunctional CEI membrane structure and a preparation method thereof provided in an embodiment of the present invention realizes multifunctional synergy by combining the functions of the inner and outer layers. The double-layer composite multifunctional CEI membrane can effectively solve the multiple challenges of high-voltage positive electrodes in complex working environments, comprehensively optimize the interface stability of high-voltage positive electrode materials, and simultaneously improve the electrochemical and mechanical properties, effectively improve the interface stability of high-voltage positive electrodes, thereby improving the overall performance and working stability of high-energy density batteries and extending the cycle life of high-energy density batteries

[0042] 2. A double-layer composite multifunctional CEI membrane structure and a preparation method thereof provided in an embodiment of the present invention, wherein the inner layer of the membrane is in direct contact with the positive electrode particles, and LiF, Li 2 ZrO 3 and LiNbO 3 The advantages of the three components enable it to effectively inhibit the decomposition of the electrolyte and the dissolution of transition metal ions, enhance the conductivity of lithium ions, and improve the electrochemical stability of the positive electrode material;

[0043] 3. A double-layer composite multifunctional CEI membrane structure and a preparation method thereof provided in an embodiment of the present invention, wherein the outer layer of the membrane directly contacts the electrolyte and adopts Li 3 PO 4 As an outer protective material, it has extremely high chemical stability and can effectively isolate the electrolyte from corroding the inner film and positive electrode particles. Although its shear modulus is slightly lower at 44GPa, it has excellent corrosion resistance and mechanical strength. While providing sufficient mechanical support, it has stronger structural durability and interface bonding strength, which helps prevent the positive electrode particles from cracking and film damage due to mechanical stress caused by volume changes during the cycle, thereby avoiding the inner film from being exposed to the electrolyte due to volume changes, effectively blocking the electrolyte from corroding the positive electrode, and slowly releasing the impact of particle volume changes on the film layer;

[0044] 4. A double-layer composite multifunctional CEI membrane structure and a preparation method thereof provided in an embodiment of the present invention can significantly improve the cycle life and working stability of high energy density batteries by reasonably selecting inner and outer membrane materials and preparation methods, and provide strong support for the development of high-performance batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 A double-layer composite multifunctional CEI membrane structure is provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0047] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0048] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known materials or methods are not specifically described.

[0049] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0050] High-voltage cathode materials face multiple challenges in complex working environments, including interfacial side reactions, mechanical failure caused by volume changes, decreased electrochemical stability, and increased interfacial impedance. In order to solve the above problems:

[0051] First, as Figure 1 As shown, the present invention provides a double-layer composite multifunctional CEI membrane structure, including a composite inner layer membrane and an outer layer protective membrane sequentially constructed from bottom to top on the positive electrode surface;

[0052] The composite inner layer film includes LiF, Li 2 ZrO 3 and LiNbO 3 ;

[0053] The outer protective film is Li 3 PO 4 .

[0054] The present invention fully combines the performance characteristics of the inner and outer layer materials through the design of the double-layer membrane, and can achieve chemical, mechanical and electrochemical multiple protection of the interface.

[0055] Among them, it should be noted that Figure 1 This is just a schematic diagram of the double-layer composite membrane, and does not represent the actual internal structure of the composite inner layer membrane. Figure 1 The purpose is just to illustrate that the composite inner layer membrane contains three components.

[0056] The inner layer film of the present invention is arranged on the positive electrode surface to directly respond to the interface reaction on the positive electrode surface, and adopts LiF, Li 2 ZrO 3 and LiNbO 3The three components are compounded as the inner layer material. The properties of each component are shown in Table 1.

[0057] Table 1

[0058]

[0059] Among them, LiF has an extremely high band gap (8.72eV) and a low formation energy (-3.19eV / atom). The high band gap makes LiF have excellent electronic insulation under battery operating conditions, effectively preventing electron leakage and inhibiting electrolyte decomposition; its low formation energy ensures the chemical stability of the material, helps to prevent the dissolution of transition metal ions, and thus stabilizes the interface between the positive electrode and the electrolyte. LiF's low Poisson's ratio (0.2) indicates that the material has a small lateral deformation when subjected to force, which enables it to withstand large stresses and effectively alleviate the mechanical stress generated by the volume change of the positive electrode material during the charging and discharging process, maintaining the stability of the interface layer. In addition, LiF also has a high shear modulus (50GPa), which further enhances its ability to resist deformation and ensures the mechanical support of the film layer.

[0060] Li 2 ZrO 3 It has a medium band gap (3.73 eV) and a low formation energy (-3.038 eV / atom), which makes it chemically stable in the inner layer. 2 ZrO 3 The crystal structure provides a good lithium ion migration channel, which helps to improve ion conductivity and enhance the electrochemical stability of the membrane layer, ensuring stable operation of the battery at high voltage. 2 ZrO 3 The combination of Poisson's ratio (0.27) and shear modulus (55GPa) gives it a stronger stress relief ability, which can effectively cope with the mechanical stress caused by the volume change of the positive electrode material during the charging and discharging process, thereby reducing the interfacial stress and improving the overall stability of the film layer.

[0061] LiNbO 3 The band gap is 3.34 eV, and its high Poisson's ratio (0.29) and good elasticity provide strong interface bonding ability in the inner layer. 3 When subjected to stress, it can effectively adapt to lateral expansion while longitudinally stretching, thereby improving its adaptability to the interface structure and crack resistance. 3 It has excellent electrochemical stability, which helps to maintain the integrity of the interface film layer during long-term cycling and ensures the stability of the interface between the positive electrode and the electrolyte in a high-voltage working environment.

[0062] The inner layer film of the present invention utilizes LiF, Li 2ZrO 3 and LiNbO 3 Under high operating voltage conditions, the interfacial film can effectively inhibit the decomposition of the electrolyte and the dissolution of transition metal ions, enhance the lithium ion conductivity, and improve the electrochemical stability of the positive electrode material.

[0063] The outer layer of the present invention is arranged outside the inner layer and directly contacts with the electrolyte. 3 PO 4 As outer layer material. 3 PO 4 Has a higher band gap (5.82eV), significantly higher than Li 2 ZrO 3 and LiNbO 3 , which means that it has excellent electronic insulation and can effectively prevent the flow of electrons, thereby reducing the decomposition reaction of the electrolyte and the occurrence of side reactions. 3 PO 4 It also has high chemical stability, which can effectively isolate the electrolyte from corroding the inner layer membrane and positive electrode particles, ensuring the long-term stability of the interface.

[0064] The double-layer composite multifunctional CEI membrane of the present invention has an inner layer directly in contact with the positive electrode particles, and utilizes LiF, Li 2 ZrO 3 and LiNbO 3 The excellent mechanical properties and low formation energy provide chemical barrier, electrochemical stability and stress relief functions. 3 PO 4 As a protective barrier, combined with its high band gap and excellent chemical stability, it further improves the corrosion resistance, mechanical strength and long-term stability of the overall film layer. Through the synergistic effect of the inner and outer layer materials, the double-layer composite multifunctional CEI membrane can effectively solve the multiple challenges of high-voltage positive electrodes in complex working environments, comprehensively optimize the interfacial stability of high-voltage positive electrode materials, and improve the electrochemical and mechanical properties at the same time, effectively improving the interfacial stability of high-voltage positive electrodes, thereby improving the overall performance and working stability of high-energy density batteries and extending the cycle life of high-energy density batteries.

[0065] In a specific embodiment, the composite inner layer film contains LiF, Li 2 ZrO 3 and LiNbO 3 The compound ratio is 1:0.5-1:0.5-1.

[0066] The ratio of each component in the present invention is creatively optimized to balance the advantages of each component. LiF provides good electrochemical stability and high electronic insulation, which can effectively prevent the decomposition of the electrolyte and the dissolution of transition metal ions.2 ZrO 3 and LiNbO 3 The main purpose is to enhance the corrosion resistance, mechanical strength and thermal stability of the membrane. The proportional design ensures that the membrane has excellent stability and a long service life in a high voltage environment.

[0067] If Li 2 ZrO 3 If the ratio of LiNbO is too high, the membrane will be too dense, which may inhibit the migration of lithium ions, thereby affecting the ionic conductivity of the electrolyte and reducing the charge and discharge efficiency of the battery. 3 Too high a ratio may make the membrane too rigid, causing cracks in the membrane during battery charge and discharge, affecting the integrity of the membrane and the long-term stability of the battery. 2 ZrO 3 and LiNbO 3 If the ratio is too low, the corrosion resistance and thermal stability of the membrane are insufficient, and the membrane is prone to degradation or rupture under high voltage or high temperature environment, thus affecting battery performance and safety.

[0068] Therefore, the optimized ratio of 1:0.5-1:0.5-1 can improve battery performance while ensuring the comprehensive stability and reliability of the membrane, and effectively improve the overall safety and service life of the battery.

[0069] In a specific embodiment, the thickness of the composite inner layer film is 30 to 50 nm, and the thickness of the outer protective film is 50 to 80 nm.

[0070] The composite inner layer membrane is mainly responsible for the electrochemical reaction, provides ionic conductivity, and stabilizes the battery interface. Therefore, a thinner inner layer membrane helps to reduce the internal resistance of the battery, improve ionic conductivity, and maintain a higher electrochemical stability.

[0071] The main function of the outer protective film is to provide mechanical strength, prevent electrolyte decomposition, and prevent the dissolution of materials such as Co. Therefore, the thickness of the film needs to be moderate to ensure sufficient corrosion resistance and mechanical strength without affecting the overall performance of the battery.

[0072] In a second aspect, the present invention provides a method for preparing a double-layer composite multifunctional CEI membrane structure, comprising the following steps:

[0073] (1) Select a high-voltage positive electrode material as the substrate; first, clean the substrate surface to remove impurities, and dry it to ensure that there is no moisture and impurities on the substrate surface to ensure uniformity and adhesion during film deposition.

[0074] (2) LiF, Li 2 ZrO 3 and LiNbO 3The powders are mixed in a predetermined ratio to form a uniform suspension, wherein the dispersant is one of ethanol and deionized water; to ensure uniform dispersion of the powder, an appropriate amount of surfactant is added (the surfactant is one of the series of sodium dodecyl sulfate (SLS), polyvinyl alcohol (PVA), and Tween (Tween)), and ultrasonic treatment is used to ensure uniform dispersion of the powder and avoid agglomeration of particles.

[0075] (3) Introducing the prepared suspension into a fluidizing tank, and spraying the suspension onto the surface of the substrate by controlling the airflow; the airflow in the fluidizing tank helps the particles to be evenly distributed on the surface of the substrate to form a uniform inner layer of film; by adjusting the airflow rate, spraying time and coating liquid concentration, the uniformity and density of the film layer are ensured; the particles are in a fluidized state under the action of the airflow, and a good coating effect can be obtained.

[0076] (4) After spraying, the inner layer film is subjected to low temperature annealing treatment at a temperature range of 200-300° C. for 1-2 hours to optimize the crystal structure and interface bonding strength of the film layer, improve the conductivity and stability of the film layer, and obtain a composite inner layer film.

[0077] (5) After the composite inner layer film has been deposited and stabilized on the substrate surface, the target material in the magnetron sputtering equipment is replaced with Li 3 PO 4 , ensure the cleanliness of the cavity and avoid cross contamination; set the sputtering process parameters: use argon as the sputtering gas in the cavity, adjust the pressure to 0.8-1.2Pa, the sputtering power to 50-120W, the substrate temperature to 100-150℃, and the sputtering time to 20-40 minutes; the outer layer film will be evenly deposited on the surface of the substrate coated with the composite inner layer film through magnetron sputtering technology.

[0078] (6) After sputtering, low-temperature annealing is performed. The annealing temperature range is 200-300°C, and the annealing time is 1-2 hours to obtain an outer protective film. Through annealing, the mechanical stability and corrosion resistance of the outer film can be improved, and the bonding force between the outer film and the inner film can be enhanced, ensuring the overall stability and durability of the film layer.

[0079] Example 1

[0080] The embodiment of the present invention provides a method for preparing a double-layer composite multifunctional CEI membrane structure, comprising the following steps:

[0081] (1) Inner membrane material ratio and preparation

[0082] LiF、Li 2 ZrO 3 and LiNbO 3The mixture was mixed in a ratio of 1:0.8:0.7, and the mixed powder was processed by ball milling for 4 hours to ensure uniform mixing of the particles. Ethanol was selected as the dispersion medium for preparing the suspension, and 0.1% of the surfactant sodium dodecyl sulfate (SLS) was added, and a uniform suspension was obtained by ultrasonic dispersion for 30 minutes.

[0083] (2) Fluidized tank coating

[0084] The high voltage cathode material (LiCoO 2 ) particles are placed in a fluidized tank, and the particles in the tank are kept evenly suspended. The suspension is evenly sprayed into the fluidized tank through an aerosol spray device. The spraying rate is set to 5 mL / min. After spraying, it is heated to 100°C and maintained for 20 minutes for rapid drying.

[0085] (3) Post-processing

[0086] After coating, the cathode material particles were heated to 250°C for annealing for 1 hour to promote the interface bonding of the inner layer film material and the optimization of the cathode material crystal structure.

[0087] (4) Preparation of outer layer film. After the inner layer film is prepared, the outer layer Li is deposited by magnetron sputtering. 3 PO 4 The sputtering conditions of the film were argon pressure 0.9 Pa, power 80 W, substrate temperature 120 ° C, sputtering time 30 min, and finally annealing at 250 ° C for 1 h.

[0088] Example 2

[0089] The embodiment of the present invention provides a method for preparing a double-layer composite multifunctional CEI membrane structure, comprising the following steps:

[0090] (1) Inner membrane material ratio and preparation

[0091] LiF、Li 2 ZrO 3 and LiNbO 3 Mixing in a ratio of 1:0.6:0.6 tends to improve the conductivity of the film layer; the mixed powder is processed by ball milling for 4 hours to ensure uniform mixing of the particles. When preparing the suspension, ethanol is used as the dispersion medium, and 0.1% of the surfactant polyvinyl alcohol (PVA) is added, and a uniform suspension is obtained by ultrasonic dispersion for 30 minutes.

[0092] (2) Fluidized tank coating

[0093] The high voltage cathode material (LiCoO 2) particles are placed in a fluidized tank, and the particles in the tank are kept evenly suspended. The suspension is evenly sprayed into the fluidized tank through an aerosol spray device. The spraying rate is set to 8 mL / min. After spraying, it is heated to 120°C and kept for 15 minutes for rapid drying to optimize the deposition efficiency and uniformity of the inner film.

[0094] (3) Post-processing

[0095] After coating, the cathode material particles were heated to 250°C for annealing for 1 hour to promote the interface bonding of the inner layer film material and the optimization of the cathode material crystal structure.

[0096] (4) Preparation of outer layer film. After the inner layer film is prepared, the outer layer Li is deposited by magnetron sputtering. 3 PO 4 The sputtering conditions of the film were argon pressure 0.9 Pa, power 80 W, substrate temperature 120 ° C, sputtering time 30 min, and finally annealing at 250 ° C for 1 h.

[0097] Example 3

[0098] The embodiment of the present invention provides a method for preparing a double-layer composite multifunctional CEI membrane structure, comprising the following steps:

[0099] (1) Inner membrane material ratio and preparation

[0100] LiF、Li 2 ZrO 3 and LiNbO 3 The mixture was mixed in a ratio of 1:1:1 to enhance the corrosion resistance and interface stability of the inner film; the mixed powder was processed by ball milling for 4 hours to ensure uniform mixing of the particles. When preparing the suspension, a mixed solvent of ethanol and deionized water (ratio 3:2) was selected as the dispersion medium to improve the dispersion effect of the powder and reduce the solvent evaporation rate to optimize the film formation process. 0.1% of the surfactant sodium dodecyl sulfate (SLS) was added and a uniform suspension was obtained by ultrasonic dispersion for 30 minutes.

[0101] (2) Fluidized tank coating

[0102] The high voltage cathode material (LiCoO 2 ) particles are placed in a fluidized tank, and the particles in the tank are kept evenly suspended. The suspension is evenly sprayed into the fluidized tank through an aerosol spray device. The spraying rate is set to 6 mL / min. After spraying, it is heated to 90°C and kept for 30 minutes for rapid drying to ensure that the film covers the surface of the positive electrode material particles more evenly.

[0103] (3) Post-processing

[0104] After coating, the cathode material particles were heated to 250°C for annealing for 1 hour to promote the interface bonding of the inner layer film material and the optimization of the cathode material crystal structure.

[0105] (4) Preparation of outer layer film. After the inner layer film is prepared, the outer layer Li is deposited by magnetron sputtering. 3 PO 4 The sputtering conditions of the film were argon pressure 0.9 Pa, power 80 W, substrate temperature 120 ° C, sputtering time 30 min, and finally annealing at 250 ° C for 1 h.

[0106] Comparative Example 1

[0107] This comparative example provides a CEI membrane structure, which is different from Example 1 in that only the suspension containing LiF is sprayed onto the surface of the positive electrode substrate to form an inner layer membrane, and then Li 3 PO 4 As outer membrane.

[0108] Comparative Example 2

[0109] This comparative example provides a CEI membrane structure, which is different from Example 1 in that only LiF, Li 2 ZrO 3 and LiNbO 3 The mixed suspension is sprayed onto the surface of the positive electrode substrate to form a CEI film without spraying the outer film.

[0110] Comparative Example 3

[0111] This comparative example provides a CEI membrane structure, which is different from Example 1 in that only Li 3 PO 4 The suspension is sprayed onto the surface of the cathode substrate to form a CEI film without an inner film.

[0112] Comparative Example 4

[0113] This comparative example provides a CEI membrane structure, which is different from Example 1 in that: LiF, Li 2 ZrO 3 and LiNbO 3 The ratio is 1:2:2

[0114] After the membranes of Examples 1-3 and Comparative Examples 1-4 were prepared, the membrane layers were comprehensively evaluated by a variety of characterization methods to ensure that the membrane layers met the actual requirements of high-voltage positive electrodes. Specifically, the annealed substrate was placed under an atomic force microscope (AFM), and the surface of the electrode coated with the CEI membrane was mechanically tested using a force-displacement curve measurement method, and the Young's modulus of the membrane layer was further calculated to evaluate its mechanical strength. Subsequently, the prepared electrodes were assembled into button cells and subjected to a series of performance tests, including interface impedance, cycle stability, and rate performance, to comprehensively evaluate the performance of the membrane layer in practical applications. The test results are shown in Table 2 below.

[0115] Table 2

[0116]

[0117] From the data in Table 2, it can be seen that although Comparative Example 1 prepared a double-layer membrane structure, the inner membrane was only sprayed with a single component of LiF, so the mechanical properties and electrochemical properties were reduced compared with Example 1. Comparative Example 2 prepared the same inner membrane as Example 1, but did not set the outer membrane, so its mechanical properties and electrochemical properties were significantly reduced. Compared with Example 1, Comparative Example 3 only has an outer membrane layer, so the mechanical properties and electrochemical properties are significantly reduced compared with Example 1; the difference between Comparative Example 4 and Example 1 is that the proportions of the components in the inner membrane layer are different. In Comparative Example 4, Li 2 ZrO 3 and LiNbO 3 The content is much higher than that in Example 1, and it can be seen that the mechanical properties and electrochemical properties are also reduced.

[0118] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A double-layer composite multifunctional CEI membrane structure, characterized in that: It includes a composite inner layer film and an outer layer protective film sequentially constructed from bottom to top on the positive electrode surface; The composite inner layer film includes LiF, Li2ZrO3 and LiNbO3; The outer protective film is Li3PO4.

2. A double-layer composite multifunctional CEI membrane structure according to claim, characterized in that: The composite ratio of LiF, Li2ZrO3 and LiNbO3 in the composite inner layer film is 1:0.5-1:0.5-1.

3. A double-layer composite multifunctional CEI membrane structure according to claim, characterized in that: The thickness of the composite inner layer film is 30-50 nm, and the thickness of the outer protective film is 50-80 nm.

4. The method for preparing a double-layer composite multifunctional CEI membrane structure according to any one of claims 1 to 3, characterized in that: The steps include: (1) coating the composite inner layer film on the positive electrode surface by a fluidized bed method; (2) The outer protective film is prepared on the prepared composite inner layer film by magnetron sputtering.

5. The method for preparing a double-layer composite multifunctional CEI membrane structure according to claim 4, characterized in that: The specific method of step (1) is as follows: LiF, Li2ZrO3 and LiNbO3 are mixed in proportion and added into a dispersing solvent to form a uniform suspension; The suspension is introduced into a fluidizing tank and sprayed onto the surface of the cathode material substrate to form a film layer; The film layer is subjected to low temperature annealing treatment to obtain a composite inner layer film.

6. The method for preparing a double-layer composite multifunctional CEI membrane structure according to claim 5, characterized in that: The dispersion solvent is ethanol or water, and a surfactant is added into the suspension.

7. The method for preparing a double-layer composite multifunctional CEI membrane structure according to claim 6, characterized in that: The surfactant is one of sodium lauryl sulfate, polyvinyl alcohol, and Tween series.

8. The method for preparing a double-layer composite multifunctional CEI membrane structure according to claim 5, characterized in that: The low temperature annealing treatment conditions are annealing temperature 200-300°C and annealing time 1-2h.

9. The method for preparing a double-layer composite multifunctional CEI membrane structure according to claim 4, characterized in that: The specific method of step (2) is as follows: The cathode material substrate with the prepared composite inner layer film is placed in a magnetron sputtering device, the target material is set to Li3PO4, and the sputtering process parameters are: argon is used as the sputtering gas in the chamber, the pressure is 0.8-1.2Pa, the sputtering power is 50-120W, the substrate temperature is 100-150℃, and the sputtering time is 20-40min; a Li3PO4 film layer is deposited on the coated composite inner layer film; The Li3PO4 film layer is subjected to low temperature annealing treatment to obtain an outer protective film.

10. The method for preparing a double-layer composite multifunctional CEI membrane structure according to claim 9, characterized in that: The low temperature annealing treatment conditions of the Li3PO4 film layer are annealing temperature 200-300°C and annealing time 1-2h.

Citation Information

Patent Citations

  • Modified high-nickel positive electrode material, preparation method and application thereof, and lithium ion battery

    CN116130664A

  • Modified ternary positive electrode material applied to all-solid-state battery, preparation method of modified ternary positive electrode material and all-solid-state battery

    CN117790780A

  • Multifunctional multi-region composite CEI film and preparation method and application thereof

    CN119050359A

  • Work with multi layers coating films and method of forming multi layers coating films

    CN1935502A

  • Modified lithium manganese iron phosphate positive electrode material and preparation method and application thereof

    US20230411607A1